A Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 and its preparation method and application

By using Z-type ternary photocatalyst TiO2/MIL-88A(Fe)/g-C3N4, the problems of slow electron transfer rate and high electron-hole pair recombination rate under visible light of existing TiO2/g-C3N4 composite materials are solved. , an efficient nitrogen reduction reaction was achieved, and the ammonia yield was significantly increased.

CN116273201BActive Publication Date: 2025-01-21DALIAN NATIONALITIES UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310091574.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-10
Publication Date
2025-01-21
Estimated Expiration
2043-02-10

AI Technical Summary

Technical Problem

The existing TiO2/g-C3N4 composite materials have problems with slow electron transfer rate and high electron-hole recombination rate under visible light irradiation, which affects the efficiency of nitrogen reduction reaction.

Method used

Z-type ternary photocatalyst TiO2/MIL-88A(Fe)/g-C3N4 was used to prepare g-C3N4 nanosheets through solvothermal method, and TiO2 particles and g-C3N4 were loaded on MIL-88A(Fe ), a direct Z-type heterojunction is formed to improve the photoadsorption capacity and electron-hole separation efficiency of the photocatalyst.

Benefits of technology

The yield and efficiency of photocatalytic nitrogen reduction are significantly improved. Compared with traditional photocatalysts, it shows the best performance in NH3 generation, and the ammonia yield can reach 1084.31 μmol/(g·h).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116273201B_ABST
    Figure CN116273201B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental chemical photocatalytic water treatment, discloses a Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 and a preparation method and application thereof, adopts a solvothermal method to prepare g-C3N4 nanosheets, and then adopts a hydrothermal method to load TiO2 particles and g-C3N4 nanosheets on MIL-88A(Fe), and through characterization, it is proved that the Z-type TiO2 / MIL-88A(Fe) / g-C3N4 has a wide light absorption range, which can promote h + , ·OH and O2· ‑ Generation. TiO2 / MIL‑88A(Fe) / g‑C3N4 can degrade Rhodamine B by more than 95% within 90 minutes. According to the N2 reduction data, under simulated sunlight irradiation, TiO2 / MIL‑88A(Fe) / g‑C3N4 has better nitrogen reduction ability than pure samples and binary complexes, and its NH3 generation is 1084.31 μmol / (g·h), which is 33.86 times that of pure TiO2 and 13.94 times that of pure g‑C3N4 nanosheets. The ternary photocatalyst TiO2 / MIL‑88A(Fe) / g‑C3N4 synthesized according to these experimental results improves the separation efficiency of photoinduced electrons and holes and has good charge transfer ability. Its good photocatalytic performance and N2 reduction performance provide new ideas for subsequent NRR.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental chemical photocatalytic water treatment, relates to generating clean gas by visible light treatment, and particularly relates to a Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 and a preparation method and application thereof. Background Art

[0002] Ammonia (NH3) is one of the most important chemicals in human activities and the ecological environment because it can be used as an intermediate for fertilizers and storage of clean energy nitrogen sources. Although N2 accounts for about 78% of the atmosphere, the main problem in synthesizing NH3 from N2 is to effectively destroy the stable N≡N bond with a bond energy of 945 kJ / mol. In the past, Harber Bosch catalysts were commonly used for industrial production of NH3, but they had to be carried out at high temperatures and high pressures (700°K-850°K, 50-200atm). This means that a large amount of material resources are required to meet the production conditions, and a large amount of gas produced will be discharged into the air. Therefore, efficiently promoting the dissociation of N2 is of great research significance.

[0003] Using sunlight, N2 can be converted into NH3 to achieve nitrogen fixation. Photocatalytic synthesis of NH3 is both environmentally friendly and energy-saving, and has been a research hotspot in recent years. Like H2 generation and CO2 reduction, NRR is excited by solar energy to produce photogenerated electron and hole pairs. The photoexcited electrons move to the catalyst surface and participate in some reduction reactions. In order to improve the efficiency of photocatalysis, it is necessary to improve the photocatalytic reaction rate and the energy efficiency of sunlight utilization. In 1972, Fujishima and Honda were able to decompose water in n-type semiconductor TiO2 single crystal electrodes under light irradiation, which opened the prelude to the research of photocatalytic technology. In 1977, Schrauzer et al. found that NRR could occur on photocatalysts under ultraviolet light irradiation through Fe loading on TiO2. Misawa et al. reported ammonia synthesis under visible light using plasmon-induced charge separation at the Au / SrTiO3 interface. Due to the huge energy required for N≡N cracking, people have been studying new catalysts to improve nitrogen reduction efficiency.

[0004] As a non-metallic polymer, g-C3N4 nanosheets are an ideal photocatalyst with good visible light response and appropriate band gap (Eg), which has great application in nitrogen reduction. For example, narrow visible light response array, photoexcited electron-hole pair recombination, low quantum efficiency and other factors will affect the photocatalytic activity of g-C3N4. Therefore, the catalytic activity is improved by coupling with other semiconductor materials. Due to the electronic structure of TiO2, it is easy to form a heterojunction with g-C3N4. The formation of its heterojunction improves the photocatalytic efficiency and expands the light absorption range. Ivana et al. prepared g-C3N4 by thermal annealing and TiO2 by thermal hydrolysis, and the N2O conversion rate was 70.6% after irradiation for 20 hours. In addition, Liu et al. reported the MXene derivative TiO2@C / g-C3N4 heterojunction for the first time, which proved to be a powerful photocatalyst for NRR. The ammonia generation rate can reach 250.6 μmol / (g·h). However, TiO2 / g-C3N4 composites suffer from slow electron transfer rate and high electron-hole pair recombination rate under visible light irradiation. Summary of the invention

[0005] Combinations of g-C3N4 and TiO2 with a variety of different techniques can improve the photocatalytic efficiency, such as metal / noble metal, non-metal, and semiconductor combinations. For example, Sadanadam et al. prepared Fe-doped TiO2 by impregnation and Fe-doped TiO2 and g-C3N4 by solid phase dispersion. Their photocatalytic effects have been greatly improved. The increase in hydrogen generation can be attributed to the Fe 3+ , synergistic effect between Ti and g-C3N4. In addition, iron-based metal organic frameworks (MOFs) are a type of heterogeneous Fenton-like materials, including MIL-101(Fe), MIL-100(Fe), MIL-53(Fe), MIL-88b(Fe) and MIL-88A(Fe). MIL-88A(Fe) is composed of iron(III) chloride hexahydrate and fumaric acid, and has good swelling effect, visible light response and good stability.

[0006] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a Z-type TiO2 / MIL-88A(Fe) / g-C3N4 catalyst and preparation method having good photocatalytic properties and good performance in nitrogen reduction, which can provide new ideas for subsequent NRR.

[0007] The present invention mainly achieves the above-mentioned object by improving the catalyst composition and preparation method. In order to achieve this object, the present invention provides:

[0008] A Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 is composed of TiO2 particles and MIL-88A(Fe) crystals loaded on g-C3N4 nanosheet units, wherein the average particle size of the TiO2 particles is 20 nm, and the MIL-88A(Fe) crystals are hexagonal rods with an average length of 4 μm.

[0009] On the other hand, a method for preparing the above-mentioned Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 is provided, wherein g-C3N4 nanosheets are prepared by a solvothermal method, and TiO2 particles and g-C3N4 nanosheets are loaded on MIL-88A(Fe) by a hydrothermal method, comprising the following steps:

[0010] (1) 10 g of melamine was added to an alumina crucible and placed in a muffle furnace, calcined at 550 ° C for 4 h, and then the product was ground into powder after naturally cooling to room temperature. It was heated to 520 ° C at 5 ° C / min and calcined in a muffle furnace for 2 h. After cooling, the powder was dispersed in 1 mol / L hydrochloric acid and ultrasonically treated for 1 h, then vigorously stirred for 8 h, filtered and freeze-dried to form g-C3N4 nanosheets;

[0011] (2) g-C3N4 and TiO2 particles were dissolved in an ethanol-water solution at a mass ratio of 1:1, and stirred for 10 minutes. Then, fumaric acid and FeCl3·6H2O were added in sequence. After stirring for 2 hours, the solution was transferred to a polytetrafluoroethylene reactor and heated at 85°C for 2 hours. After natural cooling, the solution was centrifuged at high speed. The obtained solid was washed with ethanol for 3 hours and then with deionized water for 3 hours. The solid obtained after three cycles was dried at 100°C for 10 hours. At this time, the obtained product was TiO2 / MIL-88A(Fe) / g-C3N 44 .

[0012] Furthermore, in step (2), the ethanol-water solution V 乙醇 :V 水 =1:2.

[0013] Furthermore, the amount of FeCl3·6H2O added in step (2) satisfies that the amount of Fe substance is the same as the amount of Ti substance in the TiO2 particles.

[0014] Furthermore, in the step (2), the mass ratio of fumaric acid to FeCl3·6H2O is 1:1.

[0015] On the other hand, the invention provides an application of a Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 in photocatalytic N2 reduction of NH3. 20 mg of Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 powder is added to 100 mL of a methanol-water solution containing 20% ​​methanol by volume, dispersed in a quartz tube, and ultrasonicated in an ultrasonic machine for 30 min to form a uniform suspension. Pure N2 (99.999%) is bubbled through the solution in the dark for 30 min, and N2 is maintained at 30 mL min -1 The flow rate was set to reach nitrogen saturation, and then the solution was irradiated with a xenon lamp to simulate sunlight under magnetic stirring. N2 was fixed at room temperature, and the flow of cooling water was ensured to keep the reaction container at 25°C.

[0016] Finally, the NH in the reaction vessel was measured using the indophenol blue method. 4+ concentration.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] 1. The Z-type TiO2 / MIL-88A(Fe) / g-C3N4 ternary catalyst consists of TiO2 particles with an average particle size of 20 nm and hexagonal rod-shaped MIL-88A(Fe) crystals with an average length of about 4 μm, which are loaded on g-C3N4 nanosheet units.

[0019] 2. The Z-type TiO2 / MIL-88A(Fe) / g-C3N4 ternary catalyst has strong light adsorption capacity and high electron-hole separation efficiency, mainly because the direct Z-type heterojunction material forms a direct Z-type heterojunction at the interface of the three without the introduction of a conductive medium. The key to forming a direct Z-type heterojunction is that the three semiconductor materials have a suitable band structure and the bands of the three are matched. In this way, the material structure is stable, the photogenerated carrier transmission is fast, and the recombination of photogenerated carriers can be effectively suppressed.

[0020] 3. Compared with traditional photocatalyst titanium dioxide and pure MIL-88A(Fe) and g-C3N4, the Z-type TiO2 / MIL-88A(Fe) / g-C3N4 ternary catalyst has better visible light absorption performance and greatly improves the photocatalytic nitrogen reduction yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 X-ray diffraction patterns of MIL-88A(Fe), g-C3N4, TiO2, MIL-88A(Fe) / g-C3N4, TiO2 / MIL-88A(Fe) and TiO2 / MIL-88A(Fe) / g-C3N4 in Example 1;

[0022] Figure 2 X-ray photoelectron spectra of TiO2 / MIL-88A(Fe) / g-C3N4 corresponding to TiO2, MIL-88A(Fe) and g-C3N4 in Example 1 and infrared spectra of all samples;

[0023] Figure 3 Scanning electron microscope images of g-C3N4, TiO2, MIL-88A(Fe), MIL-88A(Fe) / g-C3N4, TiO2 / MIL-88A(Fe) and TiO2 / MIL-88A(Fe) / g-C3N4 in Example 1.

[0024] Figure 4 TEM image and mapping image of TiO2 / MIL-88A(Fe) / g-C3N4 in Example 1;

[0025] Figure 5 UV-visible diffuse reflectance spectra and optical band gap diagrams of all samples in Example 1;

[0026] Figure 6 The photoluminescence spectra and It curve Nyquist plots of all samples in Example 1;

[0027] Figure 7 Comparison of NH3 yields in Example 1, and the time course of NH3 yields on different catalysts under simulated sunlight irradiation; NH3 yield recovery test of TiO2 / MIL-88A(Fe) / g-C3N4;

[0028] Figure 8 Schematic diagram of the ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 in Example 1, the Gibbs free energy of nitrogen reduction, and the three sites of TiO2 / g-C3N4, TiO2 / MIL-88A(Fe) and c;

[0029] Fig. 9 DMPO-O2 on TiO2 / MIL-88A(Fe) / g-C3N4 under simulated sunlight in Example 1 - (a), DMPO-·OH (b), and DMPO-h + Electron spin resonance spectroscopy;

[0030] Fig.10 The UV photoelectron spectra and valence band X-ray photoelectron spectra of TiO2, MIL-88A(Fe), and g-C3N4 in Example 1;

[0031] Fig.11 This is the degradation and N2 reduction principle and band gap diagram of TiO2 / MIL-88A(Fe) / g-C3N4 in Z scheme in Example 1. DETAILED DESCRIPTION

[0032] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels.

[0033] A Z-type TiO2 / MIL-88A(Fe) / g-C3N4 catalyst is composed of TiO2 particles with an average particle size of 20nm and hexagonal rod-shaped MIL-88A(Fe) crystals with an average length of about 4μm, which are loaded on g-C3N4 nanosheet units.

[0034] The preparation method of Z-type TiO2 / MIL-88A(Fe) / g-C3N4 catalyst is as follows:

[0035] (1) 10 g of melamine was added to an alumina crucible and placed in a muffle furnace and calcined at 550 °C for 4 h. The product was then ground into powder after naturally cooling to room temperature. Again, it was heated to 520 °C at 5 °C / min and calcined in a muffle furnace for 2 h. After cooling, the powder was dispersed in 1 mol / L hydrochloric acid and ultrasonically treated for 1 h, then vigorously stirred for 8 h, filtered and freeze-dried to form g-C3N4 nanosheets;

[0036] (2) Dissolve g-C3N4 and TiO2 (commercial P25) in an ethanol-water solution (V 乙醇 :V 水 =1:2), stirred thoroughly for 10 minutes, and then fumaric acid and FeCl3·6H2O were added in sequence. After stirring for 2 hours, the solution was transferred to a 50mL polytetrafluoroethylene reactor, heated at 85°C for 2 hours, naturally cooled and centrifuged at high speed, and the obtained solid was washed with ethanol for 3 hours, and then washed with deionized water for 3 hours. The solid obtained after three cycles was placed in a vacuum drying oven and dried at 100°C for 10 hours. At this time, the obtained product is TiO2 / MIL-88A(Fe) / g-C3N4.

[0037] Application of Z-type TiO2 / MIL-88A(Fe) / g-C3N4 catalyst

[0038] The Z-type TiO2 / MIL-88A(Fe) / g-C3N4 ternary catalyst was applied to photocatalytic nitrogen reduction. 20 mg of Z-type TiO2 / MIL-88A(Fe) / g-C3N4 ternary catalyst powder was added to 100 ml of methanol-water solution containing 20% ​​methanol and dispersed in a quartz tube. The solution was ultrasonicated for 30 min in an ultrasonic machine to form a uniform suspension. Pure N2 (99.999%) was bubbled through the solution for 30 min in the dark, and the N2 was maintained at 30 ml min. -1 The flow rate was set to reach nitrogen saturation. Then, a xenon lamp was used to simulate sunlight under magnetic stirring to irradiate the solution. N2 was fixed at room temperature, and cooling water was kept flowing during the experiment to keep the reaction container at 25°C. Finally, the indophenol blue method was used to determine the NH4 in the reaction container. + concentration.

[0039] Example 1

[0040] The preparation method of Z-type TiO2 / MIL-88A(Fe) / g-C3N4 catalyst is as follows:

[0041] (1) 10 g of melamine was added to an alumina crucible and placed in a muffle furnace and calcined at 550 °C for 4 h. The product was then ground into powder after naturally cooling to room temperature. Again, it was heated to 520 °C at 5 °C / min and calcined in a muffle furnace for 2 h. After cooling, the powder was dispersed in 1 mol / L hydrochloric acid and ultrasonically treated for 1 h, then vigorously stirred for 8 h, filtered and freeze-dried to form g-C3N4 nanosheets;

[0042] (2) Dissolve g-C3N4 and TiO2 (commercial P25) in an ethanol-water solution (V 乙醇 :V 水 =1:2), stirred thoroughly for 10 minutes, and then fumaric acid and FeCl3·6H2O were added in sequence. After stirring for 2 hours, the solution was transferred to a 50mL polytetrafluoroethylene reactor, heated at 85°C for 2 hours, naturally cooled and centrifuged at high speed, and the obtained solid was washed with ethanol for 3 hours, and then washed with deionized water for 3 hours. The solid obtained after three cycles was placed in a vacuum drying oven and dried at 100°C for 10 hours. At this time, the obtained product is TiO2 / MIL-88A(Fe) / g-C3N4.

[0043] Figure 1X-ray diffraction spectrum of Z-type TiO2 / MIL-88A(Fe) / g-C3N4 prepared in Example 1. Two crystal planes from MIL-88A(Fe) and the (002) crystal plane of g-C3N4 and the (101) crystal plane of TiO2 can be clearly observed in TiO2 / MIL-88A(Fe) / g-C3N4. This indicates that the samples are successfully coupled together.

[0044] Figure 2 (a) X-ray photoelectron spectra of TiO2 / MIL-88A(Fe) / g-C3N4 corresponding to TiO2, MIL-88A(Fe) and g-C3N4 prepared in Example 1 and infrared spectra of all samples. The presence of C, N, O, Fe and Ti elements in the TiO2 / MIL-88A(Fe) / g-C3N4 structure is confirmed. This proves the effective coupling of the composite surface. These bonds between the TiO2 / MIL-88A(Fe) / g-C3N4 composites are conducive to high-energy electron transfer and produce a synergistic interfacial effect on the photocatalytic performance.

[0045] Figure 3 It can be observed in (a) that g-C3N4 exhibits a nanosheet structure with severe stacking and thick sheet thickness. Figure 3 From the SEM image of TiO2 in (b), it can be seen that TiO2 is spherical and granular, with an average diameter of about 20 nm, less crystallite agglomeration, and uniform particle distribution. Figure 3 (c) shows the SEM image of MIL-88A(Fe), which has high crystallinity and uniform particle size distribution, but with a small amount of fracture. Its shape is hexagonal rods, and the length of MIL-88A(Fe) crystals is about 4 μm. Their aspect ratio is about 10:1. Figure 3 (d)-(f) SEM images of TiO2 / MIL-88A(Fe) / g-C3N4. The successful addition of TiO2 and g-C3N4 samples can be observed, in which MIL-88A(Fe) still maintains a good rod shape.

[0046] Figure 4 The observation results are consistent with those of the SEM images. Figure 4 (d)-(h) are the mapping images of TiO2 / MIL-88A(Fe) / g-C3N4 composites, indicating that the elements in the composites are C, O, N, Fe and Ti, which are uniformly distributed in the samples.

[0047] Figure 5 The absorption edge of the composite material is obviously red-shifted, which means that the light absorption range of TiO2 / MIL-88A(Fe) / g-C3N4 is the largest. Figure 5As shown in (b), the band gaps of TiO2, MIL-88A(Fe), g-C3N4 and TiO2 / MIL-88A(Fe) / g-C3N4 are 2.88, 2.17, 2.50 and 2.04 eV, respectively.

[0048] Figure 6 It was observed that g-C3N4 had a strong PL intensity at about 460nm, and after coupling together, the fluorescence intensity of the ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 was significantly reduced. Figure 6 (b) shows that the separation effect of photogenerated charge carriers is good. Figure 6 As shown in (c), TiO2 / MIL-88A(Fe) / g-C3N4 has a smaller arc radius in the electrochemical impedance spectroscopy, which indicates that there is a smaller charge transfer resistance in TiO2 / MIL-88A(Fe) / g-C3N4, which improves the separation efficiency of photogenerated electron-hole pairs.

[0049] Figure 7 As shown in (a), the ammonia production rates of pure TiO2 and pure g-C3N4 are 32.026 μmol / (g·h) and 77.78 μmol / (g·h), respectively. The ammonia production rate of the ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 is the highest, reaching 1084.31 μmol / (g·h). The ammonia production rates of the binary photocatalysts TiO2 / MIL-88A(Fe) and MIL-88A(Fe) / g-C3N4 are 476.47 μmol / (g·h) and 816.34 μmol / (g·h), respectively. Figure 7 As shown in (b), the yield of NH3 in the TiO2 / MIL-88A(Fe) / g-C3N4 sample increases linearly. Figure 7 (c) It shows that the ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 has good photostability.

[0050] Figure 8 As shown in (a), the planar structure of g-C3N4 consists of 24 C and 32 N atoms. TiO2 clusters were constructed and loaded on the surface of g-C3N4, where the MIL-88A(Fe) structure was built on the other side of the TiO2 cluster. The calculation results are shown in Figure 8 As shown in (b), the formation of the ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 can effectively improve the photocatalytic activity and NRR capacity. The main reason is that the Ti site can better activate the NN bond, that is, reduce the process of N2* hydrogenation.

[0051] Fig. 9As shown in the figure, it is confirmed that the formed TiO2 / MIL-88A(Fe) / g-C3N4 can effectively improve the O2 ·- , ·OH, and h + generation efficiency.

[0052] Fig.10 As shown in (ac), the work functions (Φ) of pure TiO2, MIL-88A(Fe), and g-C3N4 can be estimated and are equal to 6.37 eV, 6.95 eV, and 5.09 eV, respectively, on the UPS data. Fig.10 As shown in (df), according to the VB-XPS data, the valence bond energies of MIL-88A(Fe), TiO2 and g-C3N4 are -0.18, 1.08 and 1.13 eV, respectively. It can be calculated that the valence band positions of TiO2, MIL-88A(Fe) and g-C3N4 are 2.95, 2.27 and 1.72 eV, respectively. The conduction band positions are -1.08, -0.30 and -0.26 eV, respectively.

[0053] Fig.11 It is inferred that the charge transfer of the Z scheme may occur. The CB of TiO2 undergoes photoinduced electron transfer through the solid-solid contact interface and recombine with the photoinduced holes in the valence band of MIL-88A(Fe). At the same time, the photoinduced electrons at the conduction band of MIL-88A(Fe) also recombine with the photoinduced holes in g-C3N4. The oxidation potential in the valence band of TiO2 and the negative reduction potential in the conduction band of g-C3N4 are retained, which infers that the redox ability of the ternary composite material is stronger. Therefore, the Z scheme TiO2 / MIL-88A(Fe) / g-C3N4 presents the spatial isolation characteristics of photogenerated electrons and holes, so it effectively enhances the photocatalytic activity of the sample NRR.

[0054] Example 2

[0055] 10 g of melamine was added to an alumina crucible and placed in a muffle furnace and calcined at 550 °C for 4 h. The product was then ground into powder after naturally cooling to room temperature. Again, it was heated to 520 °C at 5 °C / min and calcined in a muffle furnace for 2 h. After cooling, the powder was dispersed in 1 mol / L hydrochloric acid for ultrasonic treatment for 1 h, then vigorously stirred for 8 h, filtered and freeze-dried to form g-C3N4 nanosheets.

[0056] Example 3

[0057] Fumaric acid and FeCl3·6H2O were added in sequence. After stirring for 2 hours, the solution was transferred to a 50 mL polytetrafluoroethylene reactor, heated at 85°C for 2 hours, cooled naturally and centrifuged at high speed, and the obtained solid was washed with ethanol for 3 hours and then washed with deionized water for 3 hours. The solid obtained after three cycles was placed in a vacuum drying oven and dried at 100°C for 10 hours. At this time, the obtained product was MIL-88A(Fe).

[0058] Example 4

[0059] Dissolve g-C3N4 in ethanol-water solution (V 乙醇 :V 水 =1:2), stirred thoroughly for 10 minutes, and then fumaric acid and FeCl3·6H2O were added in sequence. After stirring for 2 hours, the solution was transferred to a 50mL polytetrafluoroethylene reactor, heated at 85°C for 2 hours, naturally cooled and centrifuged at high speed, and the obtained solid was washed with ethanol for 3 hours, and then washed with deionized water for 3 hours. The solid obtained after three cycles was placed in a vacuum drying oven and dried at 100°C for 10 hours. At this time, the obtained product was MIL-88A(Fe) / g-C3N4.

[0060] Example 5

[0061] TiO2 (commercial P 25 ) dissolved in ethanol-water solution (V 乙醇 :V 水 =1:2), stirred for 10 minutes, and then fumaric acid and FeCl3·6H2O were added in sequence. After stirring for 2 hours, the solution was transferred to a 50mL polytetrafluoroethylene reactor, heated at 85°C for 2 hours, cooled naturally and centrifuged at high speed, and the obtained solid was washed with ethanol for 3 hours, and then washed with deionized water for 3 hours. The solid obtained after three cycles was placed in a vacuum drying oven and dried at 100°C for 10 hours. At this time, the obtained product is TiO2 / MIL-88A(Fe).

[0062] Application Example 1

[0063] Commercial photocatalytic TiO2 (P25, purchased from Evonik Industries) was purchased and used directly in the photocatalytic reaction without any treatment.

[0064] In Example 1, 20 mg of Z-type TiO2 / MIL-88A(Fe) / g-C3N4 ternary catalyst powder was added to 100 mL of methanol-water solution containing 20% ​​methanol and dispersed in a quartz tube. Ultrasonication was performed in an ultrasonic machine for 30 min to form a uniform suspension. Pure N2 (99.999%) was bubbled through the solution for 30 min in the dark, and N2 was maintained at 30 mL min. -1The flow rate was set to reach nitrogen saturation. Then, a xenon lamp was used to simulate sunlight under magnetic stirring to irradiate the solution. N2 was fixed at room temperature, and cooling water was kept flowing during the experiment to keep the reaction vessel at 25°C. The NH in the reaction vessel was determined using the indophenol blue method. 4+ concentration.

[0065] The results show that if Figure 7 As shown in (a), the ammonia production rates of pure TiO2 and pure g-C3N4 are 32.026 μmol / (g·h) and 77.78 μmol / (g·h), respectively. The ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 has the highest ammonia production rate, which can reach 1084.31 μmol / (g·h), which is 33.68 times and 13.94 times that of pure TiO2 and g-C3N4, respectively. The ammonia production rates of the binary photocatalysts TiO2 / MIL-88A(Fe) and MIL-88A(Fe) / g-C3N4 are 476.47 μmol / (g·h) and 816.34 μmol / (g·h), respectively. It may be that the shielding effect of TiO2 and g-C3N4 loading reduces the photocatalytic activity. The ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 exhibits the best performance in NH3 generation, which is due to the significant enhancement of the coupling among TiO2, g-C3N4 and MIL-88A(Fe) leading to the efficient separation of photoinduced electrons and holes and the increase of the optical absorption range.

[0066] Through characterization, it was proved that Z-type TiO2 / MIL-88A(Fe) / g-C3N4 has a wide light absorption range, which can promote h + , ·OH and O2· - The generation of TiO2 / MIL-88A(Fe) / g-C3N4. TiO2 / MIL-88A(Fe) / g-C3N4 can degrade Rhodamine B by more than 95% within 90 minutes. According to the N2 reduction data, under simulated sunlight irradiation, TiO2 / MIL-88A(Fe) / g-C3N4 has better nitrogen reduction ability than pure samples and binary complexes, and its NH3 generation is 1084.31μmol / (g·h), which is 33.86 times that of pure TiO2 and 13.94 times that of pure g-C3N4 nanosheets. The ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 synthesized based on these experimental results improves the separation efficiency of photoinduced electrons and holes and has good charge transfer ability. Its good photocatalytic performance and N2 reduction performance provide new ideas for subsequent NRR.

[0067] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.

Claims

1. A Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4, characterized in that: It is composed of TiO2 particles and MIL-88A(Fe) crystals loaded on g-C3N4 nanosheet units, where the average particle size of TiO2 particles is 20 nm and the MIL-88A(Fe) crystals are hexagonal rods with an average length of 4 μm. The preparation method of the Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 comprises the following steps: (1) 10 g of melamine was added to an alumina crucible and placed in a muffle furnace and calcined at 550 °C for 4 h. The product was then ground into powder after naturally cooling to room temperature. It was then heated to 520 °C at 5 °C / min and calcined in a muffle furnace for 2 h. After cooling, the powder was dispersed in 1 mol / L hydrochloric acid and ultrasonically treated for 1 h, then vigorously stirred for 8 h, filtered and freeze-dried to form g-C3N4 nanosheets. (2) g-C3N4 nanosheets and TiO2 particles were dissolved in an ethanol-water solution in a mass ratio of 1:1 and stirred for 10 minutes. Then, fumaric acid and FeCl3·6H2O were added in sequence. After stirring for 2 hours, the solution was transferred to a polytetrafluoroethylene reactor and heated at 85 °C for 2 hours. After natural cooling, it was centrifuged at high speed. The obtained solid was washed with ethanol for 3 hours and then with deionized water for 3 hours. The solid obtained after three cycles was dried at 100 °C for 10 hours. The obtained product was a Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4.

2. A Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 as claimed in claim 1, characterized in that: In the step (2), the ethanol-water solution V 乙醇 :V 水 =1:

2.

3. A Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 as claimed in claim 1, characterized in that: The amount of FeCl3·6H2O added in step (2) satisfies that the amount of Fe substance is the same as the amount of Ti substance in the TiO2 particles.

4. A Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 as claimed in claim 1, characterized in that: In the step (2), the mass ratio of fumaric acid to FeCl3·6H2O is 1:

1.

5. The use of a Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 as claimed in any one of claims 1 to 4, characterized in that: Application in photocatalytic reduction of N2 to generate NH3.

6. The use of a Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 as claimed in claim 5, characterized in that: The method for photocatalytic reduction of N2 to generate NH3 is specifically as follows: 20 mg of Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 powder is added to 100 mL of a methanol-water solution containing 20% ​​methanol by volume, dispersed in a quartz tube, and ultrasonicated in an ultrasonic machine for 30 min to form a uniform suspension, pure N2 is bubbled through the solution for 30 min in the dark, and then the solution is irradiated with a xenon lamp to simulate sunlight under magnetic stirring, and N2 is fixed at room temperature. During this period, the flow of cooling water is ensured to keep the reaction container at 25°C.

7. The use of a Z-type ternary photocatalyst TiO2 / MIL-88A(Fe) / g-C3N4 as claimed in claim 6, characterized in that: When pure N2 was bubbled through the solution in the dark for 30 min, the N2 concentration was maintained at 30 mL min -1 flow rate to achieve nitrogen saturation.

Citation Information

Patent Citations

  • Titanium dioxide-iron-carbon nitride compound photo-catalyst and preparation method thereof

    CN109482217A

  • Preparation method and application of carbon nitride-titanium dioxide heterojunction material for efficiently synthesizing ammonia through visible light

    CN113649040A